Preparation method of pseudo-tetragonal-phase barium titanate nano composite powder material

Barium titanate composite graphite phase carbon trinitrogen nanopowder was prepared through solvent evaporation and high-temperature thermal polymerization, which solved the problem of low activity and high recombination rate of barium titanate nanopowder under visible light, and realized the treatment of antibiotics in wastewater. Efficient photocatalytic degradation, the degradation rate reaches more than 80%.

CN119346148APending Publication Date: 2025-01-24CHINA THREE GORGES UNIV
View PDF 0 Cites 0 Cited by

Patent Information

Application Number
CN202411265116.8
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-09-10
Publication Date
2025-01-24

AI Technical Summary

Technical Problem

The low activity and high photogenerating electron-hole pair recombination rate of existing barium titanate nanopowders as photocatalysts in visible light limit their photocatalytic effects, especially in degrading antibiotics in wastewater.

Method used

Barium titanate composite graphite phase carbon trinitrogen nanopowder is prepared through solvent evaporation and high-temperature thermal polymerization, which broadens its visible light response range, inhibits the recombination rate of photogenerated electron-hole pairs, and improves photocatalytic degradation efficiency.

Benefits of technology

Efficient photocatalytic degradation of antibiotics such as tetracycline in wastewater was achieved, with a degradation rate of more than 80%, significantly improving the photocatalytic activity of barium titanate nanopowder.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119346148A_ABST
    Figure CN119346148A_ABST
Patent Text Reader

Abstract

The invention relates to preparation and application of a barium titanate composite graphite-phase C3N4 nano-powder photocatalyst material. Adding the titanium tetrachloride solution into the sodium hydroxide solution and stirring; then adding a barium acetate solution and stirring to obtain a white substance; reacting the barium titanate precursor under oil bath stirring to obtain white powder; putting the white powder into a muffle furnace, annealing, cooling along with the furnace, and grinding to obtain barium titanate nano powder; adding the barium titanate nano powder into deionized water; then adding phenylurea and melamine, and stirring in an oil bath to gradually evaporate water to obtain a viscous mixture; and drying the viscous mixture, annealing in a muffle furnace, cooling along with the furnace, and grinding to obtain the barium titanate nano composite powder material. The barium titanate synthesized by the method exists in a pseudo-tetragonal phase structural form, barium titanate nanocomposite powder with different graphite phase C3N4 composite amounts is prepared, and the photocatalytic degradation rate of antibiotics such as tetracycline in wastewater reaches 80% or above.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention belongs to the field of preparation technology and catalytic application of pseudo-tetragonal barium titanate composite nanomaterials, and specifically relates to a pseudo-tetragonal barium titanate nanocomposite powder photocatalyst material prepared by solvent volatilization and high-temperature thermal polymerization, and the application of the material in photocatalytic degradation of antibiotics in wastewater. Background Art

[0002] Antibiotics have long been widely used in agriculture, commerce, and medicine to treat microbial infections and protect the health of humans and animals. Tetracycline (TC) is a type of antibiotic with a stable structure of four aromatic rings, which is difficult to metabolize and absorb in the intestine. Residual TC is excreted into the surrounding rivers and soil through the urine and feces of humans and animals. Antibiotics remaining in the environment will seriously threaten the safety of the environmental ecosystem. Therefore, it is imperative to find a green and efficient method for degrading antibiotics. Semiconductor photocatalytic degradation technology has received widespread attention in the field of environmental water remediation and treatment due to its advantages such as high degradation efficiency, non-toxicity, low cost, and reusability.

[0003] Nano-barium titanate powder (BaTiO3) is a kind of semiconductor material. Barium titanate has been considered as a promising photocatalyst material due to its important properties, such as excellent dielectric / ferroelectric / piezoelectric properties and perovskite structure, appropriately positioned energy bands, oxygen vacancies, flexibility, polycrystalline phases (cubic, tetragonal, orthorhombic and rhombic) and good stability. BaTiO3 has some problems in its use as a photocatalyst: (i) large band gap and low activity under visible light. (ii) The high recombination rate of photogenerated electron-hole pairs caused by strong Coulomb attraction is limited. Therefore, its own photocatalytic effect is not good. Selecting a semiconductor with a suitable band structure to construct an S-type heterojunction with BaTiO3 to form a built-in electric field and promote the directional migration of photogenerated carriers is an effective strategy to improve the activity of photocatalysts, achieve response to the visible light band, and thus effectively improve the photocatalytic activity. Summary of the invention

[0004] In order to solve the deficiencies mentioned in the above background technology, the purpose of the present invention is to provide a method for preparing barium titanate composite graphite phase carbon trinitrogen tetrakis (hereinafter referred to as BTO / CN) nanopowder, and apply it to photocatalytic degradation of antibiotics in wastewater. The BTO / CN nanopowder material is obtained by solvent volatilization and high-temperature thermal polymerization. The preparation method is simple, the visible light response range of the obtained material is broadened, the recombination rate of photogenerated electron-hole pairs is suppressed, and the efficiency of photocatalytic degradation of antibiotics in wastewater, such as tetracycline, is improved.

[0005] The purpose of the present invention can be achieved through the following technical solutions: The method for preparing BTO / CN nanopowder of the present invention comprises the following steps: S1: Add titanium tetrachloride solution into sodium hydroxide solution and stir well; S2: adding barium acetate solution and stirring to react until a white substance is obtained, which is a barium titanate precursor; S3: reacting the barium titanate precursor under stirring in an oil bath for 3-4 h to obtain a white powder; S4: placing the white powder in a muffle furnace for annealing, cooling it in the furnace, and grinding it to obtain barium titanate nanopowder; S5: Add barium titanate nanopowder into deionized water and treat with ultrasound for 30 min; S6: Melamine is then added, and water is gradually evaporated under stirring in an oil bath to obtain a viscous mixture; S7: After the viscous mixture is dried, it is placed in a muffle furnace for annealing, cooled in the furnace, and ground to obtain barium titanate composite graphite phase carbon three nitrogen four nanometer powder.

[0006] The annealing temperature is 860-940°C, the heating rate is 4-6°C / min, and the holding time is 1-2 h.

[0007] As a preferred embodiment, in step S4: the annealing temperature is 900°C, the heating rate is 5°C / min, and the holding time is 2 h.

[0008] The mass ratio of barium titanate to melamine is 0.2~3:1-2.

[0009] Phenyl urea is also added in step S6, wherein the mass ratio of barium titanate, phenyl urea and melamine is 0.2-3:0.1-0.4:1-2.

[0010] In step S7, the annealing temperature is 590-610°C, the heating rate is 4-6°C / min, and the holding time is 3-5h. As a preferred solution, in step S7: the annealing temperature is 600°C, the heating rate is 5°C / min, and the holding time is 4h.

[0011] The barium titanate composite graphite phase carbon trinitrogen tetrakis nanometer powder or the barium titanate composite graphite phase sulfur-doped carbon nitride nanometer powder material prepared by the technical scheme of the present invention is applied to the photocatalytic degradation of antibiotics such as tetracycline in wastewater.

[0012] The present invention has the following advantages: The invention adopts solvent volatilization and high temperature thermal polymerization to prepare pseudo-tetragonal barium titanate nanocomposite powder. This method is different from other methods in that the operation is simple and the reaction conditions are easy to control. The synthesized barium titanate exists in the form of a pseudo-tetragonal phase structure, and barium titanate with different graphite phase carbon tri-nitrogen tetra-composite amounts or barium titanate composite graphite phase sulfur-doped carbon nitride nanopowders are prepared, and the photocatalytic degradation rate of antibiotics such as tetracycline in wastewater reaches more than 80%.

[0013] BaTiO3 in the form of pseudo-tetragonal phase structure has spontaneous ferroelectric polarization. At the same time, an appropriate amount of carbon nitride doped with sulfur in the composite graphite phase can expand the specific surface area of ​​BaTiO3-based composite materials, change the band structure, reduce the band gap width, improve the utilization rate of visible light, and reduce the recombination rate of photogenerated electron-hole pairs. BRIEF DESCRIPTION OF THE DRAWINGS

[0014] In order to more clearly illustrate the technical solutions in the prior art or the embodiments of the present invention, the drawings required for describing the prior art or the embodiments are briefly introduced below. Obviously, for those skilled in the art, other drawings can be obtained based on these drawings without creative work. Figure 1 Schematic diagram of XRD spectra of graphite phase carbon trinitrogen tetrakis, barium titanate, and barium titanate composite graphite phase carbon trinitrogen tetrakis nanopowder materials prepared in Comparative Sample 1, Comparative Sample 2, Comparative Sample 3, and various embodiments.

[0015] Figure 2 These are SEM images of graphite phase carbon trinitrogen tetrakis, barium titanate, and barium titanate composite graphite phase carbon trinitrogen tetrakis nanopowder materials prepared in various embodiments, wherein (a) is the SEM image of comparative example 1, (b) is the SEM image of comparative example 3, and (c) is the SEM image of embodiment 4.

[0016] Figure 3 TEM image (a) and HRTEM image (b) of the barium titanate composite graphite phase carbon trinitrogen tetrakis prepared in Example 4.

[0017] Figure 4 UV-vis spectra (a) and optical band gap spectra (b) of barium titanate composite graphite phase carbon three nitrogen four nanometer powder materials prepared in Example 1, Example 2, Example 3, Example 4, and Example 5.

[0018] Figure 5 The photocatalytic degradation activity diagram of tetracycline of the graphite phase carbon trinitrogen tetrakis, barium titanate, and barium titanate composite graphite phase carbon trinitrogen tetrakis nanopowder materials prepared by comparative sample 1, comparative sample 2, comparative sample 3, and various embodiments. DETAILED DESCRIPTION

[0019] The present invention is further described in detail below in conjunction with the embodiments, and the described embodiments are only a part of the embodiments of the present invention, rather than all the embodiments. Based on the embodiments of the present invention, all other embodiments obtained by ordinary technicians in this field without creative work belong to the scope of protection of the present invention.

[0020] A method for preparing a barium titanate composite graphite phase carbon trinitrogen tetranitrate nanopowder material comprises the following steps: S1: Add titanium tetrachloride solution into sodium hydroxide solution and stir for 30 min; S2: add barium acetate solution and stir for 30 min to obtain a white substance; S3: The barium titanate precursor was reacted in an oil bath under stirring for 4 h to obtain a white powder; S4: placing the white powder in a muffle furnace for annealing and then cooling it in the furnace, and grinding it to obtain barium titanate nanopowder.

[0021] S5: Add barium titanate nanopowder into deionized water and treat with ultrasound for 30 min; S6: Melamine is then added, and water is gradually evaporated under stirring in an oil bath to obtain a viscous mixture; S7: After the viscous mixture is dried, it is placed in a muffle furnace for annealing, cooled in the furnace, and ground to obtain barium titanate composite graphite phase carbon three nitrogen four nanometer powder.

[0022] Comparative Example 1: S1: Weigh 5 g of melamine and add it into 50 ml of deionized water. Stir continuously in an oil bath to allow the water to evaporate gradually to obtain a viscous mixture. S2: Place the viscous mixture in a muffle furnace and heat it to 600 °C at a heating rate of 5 °C / min. After annealing for 4 h, cool it in the furnace and grind it to obtain graphite phase carbon trinitrogen tetranitrate nanopowder, named CN-1.

[0023] The obtained product was subjected to XRD test. Figure 1 As shown, the CN sample has the characteristic structure of graphite phase; the SEM test results are shown in Figure 2 (a) shown. Figure 4 Shown are the UV-vis spectra and optical band gap spectra of CN. The application of CN prepared in this embodiment in the degradation of antibiotics in wastewater, such as tetracycline, specifically includes the following steps: the visible light source is a 500 W xenon lamp (CHF-XM500, China). Tetracycline (TC) solution is used as an antibiotic pollutant model, the pollutant concentration is set to 30 mg / L, and the concentration of residual pollutants in the solution is determined by a UV-visible spectrophotometer. First, 50 mg of the catalyst is dispersed in 50 ml of tetracycline solution, and then stirred in a dark environment for 30 minutes to reach adsorption equilibrium. Then, under the irradiation of a xenon lamp, the organic pollutants are degraded under visible light. Samples are taken every 10 min, and the sampling volume is 5 ml each time. The entire catalytic reaction time is 60 min. After each sampling, centrifuge at 11000 r / min for 3 min with a high-speed centrifuge. After centrifugation, the peak intensity change of the maximum absorption wavelength is recorded with a UV-visible spectrophotometer.

[0024] Figure 5 The degradation activity of CN photocatalyst for TC under visible light was described. The degradation rate of tetracycline by CN powder was 34.7% within 60 min.

[0025] Comparative Example 2: S1: Weigh 1 g of phenylurea and add it to 50 ml of deionized water. Stir continuously in an oil bath to evaporate the water gradually to obtain a viscous mixture. S2: The viscous mixture was placed in a muffle furnace and heated to 600 °C at a heating rate of 5 °C / min. After annealing for 4 h, it was cooled in the furnace and ground to obtain graphite phase carbon trinitrogen tetranitrate nanopowder, which was named CN-2.

[0026] The photocatalyst of the present invention is used to degrade antibiotics in wastewater, such as tetracycline, and the specific steps are the same as the degradation reaction steps in Comparative Example 1.

[0027] Figure 5 The degradation activity of CN-2 photocatalyst for TC under visible light was described. The degradation rate of tetracycline by CN-2 powder was 33.87% within 60 min.

[0028] Comparative Example 3: S1: Weigh 0.01902 mol titanium tetrachloride and add it to 0.06 mol sodium hydroxide solution and stir for 30 min; S2: Then, 0.00951 mol barium acetate solution was added and stirred for 30 min to obtain a white substance; S3: The barium titanate precursor was reacted in an oil bath under stirring for 4 h to obtain a white powder; S4: Place the white powder in a muffle furnace and heat it to 900 °C at a heating rate of 5 °C / min. After annealing for 2 h, cool it in the furnace and grind it to obtain barium titanate nanopowder, named BTO.900 .

[0029] The obtained product was subjected to XRD test. Figure 1 As shown, BTO 900 The crystal form is a tetragonal perovskite structure. The SEM test results are as follows Figure 2 (b) shown. Figure 4 The display is BTO 900 UV-vis spectrum and optical band gap spectrum. The photocatalyst of the present invention is used to degrade antibiotics in wastewater, such as tetracycline, and the specific steps are the same as the degradation reaction steps in Comparative Example 1. Figure 5 Describes BTO 900 Photocatalytic activity of TC degradation under visible light. BTO 900 The degradation rate of tetracycline by the powder within 60 minutes is 7.45%.

[0030] Embodiment 1: S1: Weigh 0.01902 mol titanium tetrachloride and add it to 0.06 mol sodium hydroxide solution and stir for 30 min; S2: Then, 0.00951 mol barium acetate solution was added and stirred for 30 min to obtain a white substance; S3: The barium titanate precursor was reacted in an oil bath under stirring for 4 h to obtain a white powder; S4: Place the white powder in a muffle furnace and heat it to 900 °C at a heating rate of 5 °C / min. After annealing for 2 h, cool it in the furnace and grind it to obtain barium titanate nanopowder, named BTO. 900 ; S5: 0.2 g of barium titanate nanopowder was added into deionized water and ultrasonicated for 30 min; S6: Then, 2 g of melamine was added and the water was gradually evaporated under stirring in an oil bath to obtain a white viscous mixture; S7: The white viscous mixture was dried and placed in a muffle furnace, heated to 600 °C at a heating rate of 5 °C / min, annealed for 4 h, and then cooled in the furnace. The barium titanate composite graphite phase carbon trinitrogen tetranitrate nanopowder was obtained by grinding, named BTO. 900,0.2 / CN.

[0031] The obtained product was subjected to XRD test. Figure 1 As shown, BTO 900,0.2 The crystal form of BTO in the / CN sample is a tetragonal perovskite structure. Figure 4 The display is BTO 900,0.2 UV-vis spectrum and optical band gap spectrum of / CN. The photocatalyst of the present invention is used to degrade antibiotics in wastewater, such as tetracycline, and the specific steps are the same as the degradation reaction steps in Comparative Example 1.

[0032] Figure 5 Describes BTO 900,0.2 Degradation activity of TC by BTO / CN photocatalyst under visible light. 900,0.2 The degradation rate of tetracycline by / CN powder within 60 minutes is 78.46%.

[0033] Embodiment 2: S1: Weigh 0.01902 mol titanium tetrachloride and add it to 0.06 mol sodium hydroxide solution and stir for 30 min; S2: Then, 0.00951 mol barium acetate solution was added and stirred for 30 min to obtain a white substance; S3: The barium titanate precursor was reacted in an oil bath under stirring for 4 h to obtain a white powder; S4: Place the white powder in a muffle furnace and heat it to 900 °C at a heating rate of 5 °C / min. After annealing for 2 h, cool it in the furnace and grind it to obtain barium titanate nanopowder, named BTO. 900 ; S5: 0.5 g of barium titanate nanopowder was added into deionized water and ultrasonicated for 30 min; S6: Then, 2 g of melamine was added and the water was gradually evaporated under stirring in an oil bath to obtain a white viscous mixture; S7: The white viscous mixture was dried and placed in a muffle furnace, heated to 600 °C at a heating rate of 5 °C / min, annealed for 4 h, and then cooled in the furnace. The barium titanate composite graphite phase carbon trinitrogen tetranitrate nanopowder was obtained by grinding, named BTO. 900,0.5 / CN.

[0034] The obtained product was subjected to XRD test. Figure 1 As shown, BTO 900,0.5 The crystal form of BTO in the / CN sample is a tetragonal perovskite structure. Figure 4 The display is BTO 900,0.5 UV-vis spectrum and optical band gap spectrum of / CN.

[0035] The photocatalyst of the present invention is used to degrade antibiotics in wastewater, such as tetracycline, and the specific steps are the same as the degradation reaction steps in Comparative Example 1.

[0036] Figure 5 Describes BTO 900,0.5 Degradation activity of TC by BTO / CN photocatalyst under visible light. 900,0.5 The degradation rate of tetracycline by / CN powder within 60 minutes is 81.99%.

[0037] Embodiment 3: S1: Weigh 0.01902 mol titanium tetrachloride and add it to 0.06 mol sodium hydroxide solution and stir for 30 min; S2: Then, 0.00951 mol barium acetate solution was added and stirred for 30 min to obtain a white substance; S3: The barium titanate precursor was reacted in an oil bath under stirring for 4 h to obtain a white powder; S4: Place the white powder in a muffle furnace and heat it to 900 °C at a heating rate of 5 °C / min. After annealing for 2 h, cool it in the furnace and grind it to obtain barium titanate nanopowder, named BTO. 900 ; S5: 1 g of barium titanate nanopowder was added into deionized water and ultrasonicated for 30 min; S6: Then, 2 g of melamine was added and the water was gradually evaporated under stirring in an oil bath to obtain a white viscous mixture; S7: The white viscous mixture was dried and placed in a muffle furnace, heated to 600 °C at a heating rate of 5 °C / min, annealed for 4 h, and then cooled in the furnace. The barium titanate composite graphite phase carbon trinitrogen tetranitrate nanopowder was obtained by grinding, named BTO. 900,1 / CN.

[0038] The obtained product was subjected to XRD test. Figure 1 As shown, BTO 900,1 The crystal form of BTO in the / CN sample is a tetragonal perovskite structure. Figure 4 The display is BTO 900,1 UV-vis spectrum and optical band gap spectrum of / CN.

[0039] The photocatalyst of the present invention is used to degrade antibiotics in wastewater, such as tetracycline, and the specific steps are the same as the degradation reaction steps in Comparative Example 1.

[0040] Figure 5 Describes BTO 900,1 Degradation activity of TC by BTO / CN photocatalyst under visible light. 900,1 The degradation rate of tetracycline by / CN powder within 60 minutes is 83.94%.

[0041] Embodiment 4: S1: Weigh 0.01902 mol titanium tetrachloride and add it to 0.06 mol sodium hydroxide solution and stir for 30 min; S2: Then, 0.00951 mol barium acetate solution was added and stirred for 30 min to obtain a white substance; S3: The barium titanate precursor was reacted in an oil bath under stirring for 4 h to obtain a white powder; S4: Place the white powder in a muffle furnace and heat it to 900 °C at a heating rate of 5 °C / min. After annealing for 2 h, cool it in the furnace and grind it to obtain barium titanate nanopowder, named BTO. 900 ; S5: 2 g of barium titanate nanopowder was added into deionized water and ultrasonicated for 30 min; S6: Then, 2 g of melamine was added and the water was gradually evaporated under stirring in an oil bath to obtain a white viscous mixture; S7: The white viscous mixture was dried and placed in a muffle furnace, heated to 600 °C at a heating rate of 5 °C / min, annealed for 4 h, and then cooled in the furnace. The barium titanate composite graphite phase carbon trinitrogen tetranitrate nanopowder was obtained by grinding, named BTO. 900,2 / CN.

[0042] The obtained product was subjected to XRD test. Figure 1 As shown, BTO 900,2 The crystal form of BTO in the CN sample is a tetragonal perovskite structure. The SEM test results are as follows Figure 2 (c) As shown. TEM test results are shown Figure 3 shown. Figure 4 The display is BTO 900,2 UV-vis spectrum and optical band gap spectrum of / CN.

[0043] The photocatalyst of the present invention is used to degrade antibiotics in wastewater, such as tetracycline, and the specific steps are the same as the degradation reaction steps in Comparative Example 1.

[0044] Figure 5 Describes BTO 900,2 Degradation activity of TC by BTO / CN photocatalyst under visible light. 900,2 The degradation rate of tetracycline by / CN powder within 60 minutes is 91.88%.

[0045] Embodiment 5: S1: Weigh 0.01902 mol titanium tetrachloride and add it to 0.06 mol sodium hydroxide solution and stir for 30 min; S2: Then, 0.00951 mol barium acetate solution was added and stirred for 30 min to obtain a white substance; S3: The barium titanate precursor was reacted in an oil bath under stirring for 4 h to obtain a white powder; S4: Place the white powder in a muffle furnace and heat it to 900 °C at a heating rate of 5 °C / min. After annealing for 2 h, cool it in the furnace and grind it to obtain barium titanate nanopowder, named BTO. 900 ; S5: 3 g of barium titanate nanopowder was added into deionized water and ultrasonicated for 30 min; S6: Then, 2 g of melamine was added and the water was gradually evaporated under stirring in an oil bath to obtain a white viscous mixture; S7: The white viscous mixture was dried and placed in a muffle furnace, heated to 600 °C at a heating rate of 5 °C / min, annealed for 4 h, and then cooled in the furnace. The barium titanate composite graphite phase carbon trinitrogen tetranitrate nanopowder was obtained by grinding, named BTO. 900,3 / CN.

[0046] The obtained product was subjected to XRD test. Figure 1 As shown, BTO 900,3 The crystal form of BTO in the / CN sample is a tetragonal perovskite structure. Figure 4 The display is BTO 900,3 UV-vis spectrum and optical band gap spectrum of / CN.

[0047] The photocatalyst of the present invention is used to degrade antibiotics in wastewater, such as tetracycline, and the specific steps are the same as the degradation reaction steps in Comparative Example 1.

[0048] Figure 5 Describes BTO 900,3 Degradation activity of TC by BTO / CN photocatalyst under visible light. 900,3 The degradation rate of tetracycline by / CN powder within 60 minutes is 84.18%.

[0049] Embodiment 6: S1: Weigh 0.01902 mol titanium tetrachloride and add it to 0.06 mol sodium hydroxide solution and stir for 30 min; S2: Then, 0.00951 mol barium acetate solution was added and stirred for 30 min to obtain a white substance; S3: The barium titanate precursor was reacted in an oil bath under stirring for 4 h to obtain a white powder; S4: Place the white powder in a muffle furnace and heat it to 860 °C at a heating rate of 5 °C / min. After annealing for 2 h, cool it in the furnace and grind it to obtain barium titanate nanopowder, named BTO. 860 ; S5: 2 g of barium titanate nanopowder was added into deionized water and ultrasonicated for 30 min; S6: Then, 2 g of melamine was added and the water was gradually evaporated under stirring in an oil bath to obtain a white viscous mixture; S7: The white viscous mixture was dried and placed in a muffle furnace, heated to 600 °C at a heating rate of 5 °C / min, annealed for 4 h, and then cooled in the furnace. The barium titanate composite graphite phase carbon trinitrogen tetranitrate nanopowder was obtained by grinding, named BTO. 860,2 / CN.

[0050] The obtained product was subjected to XRD test. Figure 1 (b) As shown in BTO 860,2 The crystal structure of BTO in the / CN sample is cubic phase structure.

[0051] The photocatalyst of the present invention is used to degrade antibiotics in wastewater, such as tetracycline, and the specific steps are the same as the degradation reaction steps in Comparative Example 1.

[0052] Figure 5 Describes BTO 860,2 Degradation activity of TC by BTO / CN photocatalyst under visible light. 860,2 The degradation rate of tetracycline by / CN powder within 60 minutes is 61.30%.

[0053] Embodiment 7: S1: Weigh 0.01902 mol titanium tetrachloride and add it to 0.06 mol sodium hydroxide solution and stir for 30 min; S2: Then, 0.00951 mol barium acetate solution was added and stirred for 30 min to obtain a white substance; S3: The barium titanate precursor was reacted in an oil bath under stirring for 4 h to obtain a white powder; S4: Place the white powder in a muffle furnace and heat it to 880 °C at a heating rate of 5 °C / min. After annealing for 2 h, cool it in the furnace and grind it to obtain barium titanate nanopowder, named BTO. 880 ; S5: 2 g of barium titanate nanopowder was added into deionized water and ultrasonicated for 30 min; S6: Then, 2 g of melamine was added and the water was gradually evaporated under stirring in an oil bath to obtain a white viscous mixture; S7: The white viscous mixture was dried and placed in a muffle furnace, heated to 600 °C at a heating rate of 5 °C / min, annealed for 4 h, and then cooled in the furnace. The barium titanate composite graphite phase carbon trinitrogen tetranitrate nanopowder was obtained by grinding, named BTO. 880,2 / CN.

[0054] The obtained product was subjected to XRD test. Figure 1 (b) As shown in BTO 880,2 The crystal structure of BTO in the / CN sample is cubic phase structure.

[0055] The photocatalyst of the present invention is used to degrade antibiotics in wastewater, such as tetracycline, and the specific steps are the same as the degradation reaction steps in Comparative Example 1.

[0056] Figure 5 Describes BTO 880,2 Degradation activity of TC by BTO / CN photocatalyst under visible light. 880,2 The degradation rate of tetracycline by / CN powder within 60 minutes is 82.4%.

[0057] Embodiment 8: S1: Weigh 0.01902 mol titanium tetrachloride and add it to 0.06 mol sodium hydroxide solution and stir for 30 min; S2: Then, 0.00951 mol barium acetate solution was added and stirred for 30 min to obtain a white substance; S3: The barium titanate precursor was reacted in an oil bath under stirring for 4 h to obtain a white powder; S4: Place the white powder in a muffle furnace and heat it to 920 °C at a heating rate of 5 °C / min. After annealing for 2 h, cool it in the furnace and grind it to obtain barium titanate nanopowder, named BTO. 920 ; S5: 2 g of barium titanate nanopowder was added into deionized water and ultrasonicated for 30 min; S6: Then, 2 g of melamine was added and the water was gradually evaporated under stirring in an oil bath to obtain a white viscous mixture; S7: The white viscous mixture was dried and placed in a muffle furnace, heated to 600 °C at a heating rate of 5 °C / min, annealed for 4 h, and then cooled in the furnace. The barium titanate composite graphite phase carbon trinitrogen tetranitrate nanopowder was obtained by grinding, named BTO. 920,2 / CN.

[0058] The obtained product was subjected to XRD test. Figure 1 (b) As shown in BTO 920,2 The crystal structure of BTO in the / CN sample is cubic phase structure.

[0059] The photocatalyst of the present invention is used to degrade antibiotics in wastewater, such as tetracycline, and the specific steps are the same as the degradation reaction steps in Comparative Example 1.

[0060] Figure 5 Describes BTO 920,2 Degradation activity of TC by BTO / CN photocatalyst under visible light. 920,2 The degradation rate of tetracycline by / CN powder within 60 minutes is 83.03%.

[0061] Embodiment 9: S1: Weigh 0.01902 mol titanium tetrachloride and add it to 0.06 mol sodium hydroxide solution and stir for 30 min; S2: Then, 0.00951 mol barium acetate solution was added and stirred for 30 min to obtain a white substance; S3: The barium titanate precursor was reacted in an oil bath under stirring for 4 h to obtain a white powder; S4: Place the white powder in a muffle furnace and heat it to 940 °C at a heating rate of 5 °C / min. After annealing for 2 h, cool it in the furnace and grind it to obtain barium titanate nanopowder, named BTO. 940 ; S5: 2 g of barium titanate nanopowder was added into deionized water and ultrasonicated for 30 min; S6: Then, 2 g of melamine was added and the water was gradually evaporated under stirring in an oil bath to obtain a white viscous mixture; S7: The white viscous mixture was dried and placed in a muffle furnace, heated to 600 °C at a heating rate of 5 °C / min, annealed for 4 h, and then cooled in the furnace. The barium titanate composite graphite phase carbon trinitrogen tetranitrate nanopowder was obtained by grinding, named BTO. 940,2 / CN.

[0062] The obtained product was subjected to XRD test. Figure 1 (b) As shown in BTO 940,2 The crystal structure of BTO in the / CN sample is cubic phase structure.

[0063] The photocatalyst of the present invention is used to degrade antibiotics in wastewater, such as tetracycline, and the specific steps are the same as the degradation reaction steps in Comparative Example 1.

[0064] Figure 5 Describes BTO 940,2 Degradation activity of TC by BTO / CN photocatalyst under visible light. 940,2 The degradation rate of tetracycline by / CN powder within 60 minutes is 84.37%.

[0065] Embodiment 10: S1: Weigh 0.01902 mol titanium tetrachloride and add it to 0.06 mol sodium hydroxide solution and stir for 30 min; S2: Then, 0.00951 mol barium acetate solution was added and stirred for 30 min to obtain a white substance; S3: The barium titanate precursor was reacted in an oil bath under stirring for 4 h to obtain a white powder; S4: Place the white powder in a muffle furnace and heat it to 900 °C at a heating rate of 5 °C / min. After annealing for 2 h, cool it in the furnace and grind it to obtain barium titanate nanopowder, named BTO.900 ; S5: 0.2 g of barium titanate nanopowder was added into deionized water and ultrasonicated for 30 min; S6: 0.4 g of phenylurea and 2 g of melamine were then added and the water was gradually evaporated under stirring in an oil bath to obtain a white viscous mixture; S7: The white viscous mixture was dried and placed in a muffle furnace, heated to 600 °C at a heating rate of 5 °C / min, annealed for 4 h, and then cooled in the furnace. The barium titanate composite graphite phase carbon trinitrogen tetranitrate nanopowder was obtained by grinding, named BTO. 900,0.2 / CN-S-1.

[0066] The photocatalyst of the present invention is used to degrade antibiotics in wastewater, such as tetracycline, and the specific steps are the same as the degradation reaction steps in Comparative Example 1.

[0067] BTO 900,0.2 / The degradation rate of tetracycline by CN-S-1 powder within 32 minutes is 95.52%.

[0068] Embodiment 11: S1: Weigh 0.01902 mol titanium tetrachloride and add it to 0.06 mol sodium hydroxide solution and stir for 30 min; S2: Then, 0.00951 mol barium acetate solution was added and stirred for 30 min to obtain a white substance; S3: The barium titanate precursor was reacted in an oil bath under stirring for 4 h to obtain a white powder; S4: Place the white powder in a muffle furnace and heat it to 900 °C at a heating rate of 5 °C / min. After annealing for 2 h, cool it in the furnace and grind it to obtain barium titanate nanopowder, named BTO. 900 ; S5: 0.2 g of barium titanate nanopowder was added into deionized water and ultrasonicated for 30 min; S6: Then, 0.1 g of phenylurea and 2 g of melamine were added and the water was gradually evaporated under stirring in an oil bath to obtain a white viscous mixture; S7: The white viscous mixture was dried and placed in a muffle furnace, heated to 600 °C at a heating rate of 5 °C / min, annealed for 4 h, and then cooled in the furnace. The barium titanate composite graphite phase carbon trinitrogen tetranitrate nanopowder was obtained by grinding, named BTO. 900,0.2 / CN-S-2.

[0069] The photocatalyst of the present invention is used to degrade antibiotics in wastewater, such as tetracycline, and the specific steps are the same as the degradation reaction steps in Comparative Example 1.

[0070] BTO 900,0.2 / The degradation rate of tetracycline by CN-S-2 powder within 60 minutes is 88.65%.

[0071] The invention adopts solvent volatilization and high temperature thermal polymerization to prepare pseudo-tetragonal barium titanate nanocomposite powder. This method is different from other methods in that the operation is simple and the reaction conditions are easy to control. The synthesized barium titanate exists in the form of a pseudo-tetragonal phase structure, and barium titanate nanocomposite powders with different graphite phase carbon three nitrogen four composite amounts are prepared, and the photocatalytic degradation rate of antibiotics such as tetracycline in wastewater reaches more than 80%.

[0072] The present invention is described in detail above in conjunction with specific embodiments, and the basic principles, main features and advantages of the present invention are shown and described above. It should be understood by those skilled in the art that the present invention is not limited by the above embodiments, and the above embodiments and descriptions are only for explaining the principles of the present invention. Without departing from the spirit and scope of the present invention, the present invention may have various changes and improvements, and these changes and improvements all fall within the scope of the present invention to be protected.

Claims

1. A method for preparing a pseudo-tetragonal barium titanate nanocomposite powder material, characterized in that: The following steps are involved: S1: adding barium titanate nanopowder into deionized water, dispersing evenly by ultrasonication, adding melamine, stirring in an oil bath to gradually evaporate the water to obtain a viscous mixture; S2: After the viscous mixture is dried, it is placed in a muffle furnace for annealing, cooled in the furnace, and ground to obtain a barium titanate nanocomposite powder material.

2. The method for preparing a pseudo-tetragonal barium titanate nanocomposite powder material according to claim 1, characterized in that: The barium titanate nanopowder is prepared by adding a titanium tetrachloride solution to a sodium hydroxide solution and stirring evenly, and then adding a barium acetate solution and stirring to react to obtain a white barium titanate precursor. The barium titanate precursor is reacted under stirring in an oil bath to obtain white powder; the white powder is annealed in a muffle furnace, cooled along with the furnace, and ground to obtain barium titanate nanopowder.

3. The method for preparing a pseudo-tetragonal barium titanate nanocomposite powder material according to claim 2, characterized in that: The annealing temperature is 860-940°C, the heating rate is 4-6°C / min, and the holding time is 1-2 h.

4. The method for preparing a pseudo-tetragonal barium titanate nanocomposite powder material according to claim 1, characterized in that: In the step S1, the mass ratio of barium titanate to melamine is 0.2-3:1-2.

5. The method for preparing a pseudo-tetragonal barium titanate nanocomposite powder material according to claim 1, characterized in that: Phenyl urea is also added in step S1, wherein the mass ratio of barium titanate, phenyl urea and melamine is 0.2-3:0.1-0.4:1-2.

6. The method for preparing a pseudo-tetragonal barium titanate nanocomposite powder material according to claim 1, characterized in that: In step S2, the annealing temperature is 590-610°C, the heating rate is 4-6°C / min, and the holding time is 3-5 h.

7. Use of the pseudo-tetragonal barium titanate nanocomposite powder material prepared according to any one of claims 1 to 6 in the photocatalytic degradation of antibiotics in wastewater.

8. The use according to claim 7, characterized in that: The antibiotic is selected from tetracycline.